Literasi Digital sebagai Agenda Komunikasi Publik: Tinjauan Kritis Diskursus Literasi Digital di Indonesia - Gema Bastari; Lathiefah Widuri Retyaningyas; Acih Sari; Bimo Aji; Muhamad Lukman Arifianto (Jurnal Public Relations (J-PR), 2026)
This article provides a critical overview of how digital literacy is understood and applied as a public communication agenda by the Government of Indonesia. It highlights the fundamental problem of the government’s approach in developing digital literacy that tends to view digital technology as mostly a source of threat for the nation’s unity. As a result, digital literacy is often viewed as a tool by which the government can control how their citizens interact with digital technology solely according to its own vision of a ‘positive internet’. This article argues that such an approach is problematic as it fails to take into account the existing problem of digital divide as well as the various dimensions of digital literacy that can provide a solution to this problem. In the interest of promoting a more open digital society, this paper will offer an alternative approach at understanding digital literacy which goes beyond how people can better use new digital technology into how people can incorporate digital knowledge into their social life to participate in the new mode of meaning making.